Retrospective Study of Functional and Esthetic Outcomes Using Narrow-Diameter Implants for Single Upper Central Incisor Replacements - Eduardo Anitua; Aitana Tarazona; Mohammad Hamdan Alkhraisat (Dentistry Journal)
Objectives: The upper central incisors play a central role in esthetics, symmetry, and function. The purpose of this study is to evaluate the use of narrow-diameter implants (NDIs) for replacing single missing upper central incisors, addressing the gap in research regarding specific tooth types and their esthetic outcomes. Methods: This retrospective study included adult patients with a single missing upper central incisor replaced by NDIs. Exclusion criteria included patients who lost adjacent teeth during follow-up and patients with non-loaded implants. The primary outcome was peri-implant bone stability, while secondary outcomes included implant survival, technical complications, patient satisfaction, and esthetic evaluation using the Pink Esthetic Score (PES) and the White Esthetic Score (WES). Descriptive statistical analysis was performed. Results: A total of 64 NDIs were placed in 64 patients (mean age 55 ± 15 years; 40 females, 24 males). Implant diameters were 3.3 and 3.5 mm, with lengths ranging from 6.5 to 11.0 mm. The mean follow-up period was 42 ± 19 months. Marginal bone loss was −0.7 ± 0.9 mm mesially and −0.5 ± 0.7 mm distally. No implant failures were recorded. Esthetic outcomes were satisfactory, with a mean PES of 7.0 ± 2.6 and a mean WES of 7.9 ± 2.0. Conclusions: NDIs demonstrated high survival rates, marginal bone stability, and acceptable esthetic outcomes in the replacement of single upper central incisors.